Pottery with Graphic Images and Handles from the Settlement of Kizhirovo: Technological Features - Dmitry V. Selin (Нижневолжский археологический вестник)
Technical and technological analysis was conducted on four vessels with graphical images and one piece of utensil with handles from the settlement of Kizhirovo. It was revealed that the pottery was made of different types of tin clay. The only recorded recipe for the paste was clay + broken stone. The surface treatment and, partially, the molding of two vessels were done using a potter’s wheel, as evidenced by the clear parallel concentric lines of papillary traces. Graphic images were applied on wet clay with a hard tool to all the vessels before burning. On vessel 1, the composition of “brackets” was patched onto the rest of the surface. In the lower part of the pattern, there was inlay of pinkish sand grains. Petrographic analysis of vessels 1 and 3 showed that the clay for the production of these artifacts was extracted from the Dust-Karaminsky anticline located presumably not far from the settlement. The clay of these two vessels has differences in mineral composition, indicating that they were made from different types of clay. Anthropomorphic images have been found in the materials from the Beloyarka culture and the Kulaika cultural-historical community, but so far, no pottery has been found that was made using a potter’s wheel in either of these cultures or any other neighboring cultures. This testifies to the penetration into the environment of the Kizhirovo population of a group skilled in the use of the potter’s wheel for surface treatment and shaping. Probably, this group could have penetrated into the territory occupied by the Kizhirovo culture through the area of the forest-steppe Tagar culture. This is indicated by the discovery of a characteristic vessel with handles (“horned”) in the ditch of the Kizhirovo settlement. This type has been found in the grave complexes of the forest-steppe Tagar culture.